Floatable artificial leaf to couple oxygen-tolerant CO2 conversion with water purification - Zhiyong Zhang; Yang Wang; Yangen Xie; Toru Tsukamoto; Qi Zhao; Qing Huang; Xingmiao Huang; Boyang Zhang; Wenjing Song; Chuncheng Chen; Hua Sheng; Jincai Zhao (Nature Communications)
Abstract To enable open environment application of artificial photosynthesis, the direct utilization of environmental CO2 via an oxygen-tolerant reductive procedure is necessary. Herein, we introduce an in situ growth strategy for fabricating two-dimensional heterojunctions between indium porphyrin metal-organic framework (In-MOF) and single-layer graphene oxide (GO). Upon illumination, the In-MOF/GO heterostructure facilitates a tandem CO2 capture and photocatalytic reduction on its hydroxylated In-node, prioritizing the reduction of dilute CO2 even in the presence of air-level O2. The In-MOF/GO heterostructure photocatalyst is integrated with a porous polytetrafluoroethylene (PTFE) membrane to construct a floatable artificial leaf. Through a triphase photocatalytic reaction, the floatable artificial leaf can remove aqueous contaminants from real water while efficiently reducing CO2 at low concentrations (10%, approximately the CO2 concentration in combustion flue gases) upon air-level O2. This study provides a scalable approach for the construction of photocatalytic devices for CO2 conversion in open environments.